Augmented Reality-Based Interactive Educational Media for Light Fire Extinguisher Training and Enhanced Emergency Preparedness - Bima Sulistia; Rizkayeni Marta; Delvi Asmara; David Mhlanga; Dana Tsoy (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
Fire hazards are an inherent risk in every building, making it essential to understand the proper use of fire extinguishers to effectively respond, prevent the spread of fire, and minimize property damage and casualties. However, current fire extinguisher instructions are often inadequate, relying on verbal explanations or static images that are difficult to visualize. The lack of practical training due to limited facilities also results in insufficient user experience. This research aims to develop Augmented Reality (AR)-based interactive educational media to improve user understanding of light fire extinguisher training and enhance emergency preparedness. The development follows the Multimedia Development Life Cycle (MDLC) method, consisting of six stages: concept, design, material collection, assembly, testing, and distribution. The results indicate that the educational media is both highly valid and practical. Its validity is supported by the visual display, educational content, and interactivity, while its practicality is demonstrated through ease of use, time efficiency, engagement, and overall benefits. This AR-based educational media provides an innovative solution to enhance fire safety literacy and facilitate interactive learning, particularly at Universitas Negeri Padang and the broader community.